2016
DOI: 10.4028/www.scientific.net/ssp.258.574
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure Analysis and Mechanical Properties of Low Alloy High Strength Quenched and Partitioned Steel

Abstract: Abstract. Gleeble study of the quenching and partitioning (Q&P) process has been performed on Domex 960 steel (Fe, 0.08 %C, 1.79 %Mn, 0.23 %Si, 0.184 %Ti, and 0.038 %Al). The effect of different Q&P conditions on microstructure and mechanical properties were investigated. The aim of the process is to produce a fine grained microstructure for better ductility and controlled amounts of different micro-constituents to increase the strength and toughness simultaneously. Three different quenching temperatures, thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Previous studies by the authors [4,22] on the effect of Q&P after laser welding of a low-carbon steel showed that samples partitioned at a higher temperature had the best tensile properties but very low Charpy V impact toughness results. In the present work, in order to investigate the origins of such contradictory results, the abovementioned main issues are studied.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Previous studies by the authors [4,22] on the effect of Q&P after laser welding of a low-carbon steel showed that samples partitioned at a higher temperature had the best tensile properties but very low Charpy V impact toughness results. In the present work, in order to investigate the origins of such contradictory results, the abovementioned main issues are studied.…”
Section: Introductionmentioning
confidence: 90%
“…As mentioned before, the structure is made of tempered and fresh martensite lathes from the first and second quench and bainite from the partitioning stage. So, the toughness of such structure is increased by a high density of the high angle boundaries created, because this kind of boundary acts as an obstacle for cleavage propagation, forcing the cleavage crack to change its microscopic plane of propagation in order to accommodate the new local crystallography [22,36,37]. In addition, the presence of coarse martensite laths leads to early strain localization, especially when they are in the vicinity of untempered martensite islands [38].…”
Section: Grain Size Effectmentioning
confidence: 99%
“…This quench defines a specific fraction of initial martensite, and then a holding of the component at a usually higher temperature for some time gives enough energy for tempering the 'initial martensite' and partitioning of carbon from martensite to retained austenite. Subsequently, the process finishes with a second quench which may lead to the formation of 'secondary martensite' (fresh martensite) [31,32]. Owing to weldability requirements, 90% of all steels used today are alloyed with less than 0.2 wt-% C [33].…”
Section: Introductionmentioning
confidence: 99%